1982
DOI: 10.1210/endo-111-3-1010
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Hypoxia on Insulin and Glucagon Secretion in the Perfused Pancreas of the Rat

Abstract: It has been reported that insulin secretion decreases during hypoxia both in vitro and in vitro, while an increase in glucagon secretion is found only in vivo. The effect of acute hypoxia on the secretion of glucagon and insulin was studied in the perfused rat pancreas. Phentolamine, an alpha-adrenergic blocker, was perfused during the period of hypoxia to elucidate the role of alpha-adrenergic stimulation. Sodium ATP and dibutyryl cAMP were also administered to study their effects on insulin and glucagon resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

1991
1991
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 15 publications
0
14
1
Order By: Relevance
“…45,46 Indeed, previous studies have shown that hypoxia impairs insulin secretion. 52,53 Thus, these studies along with our findings and others, 27,41,42 which all show impaired b-cell function with VHL loss, are in contrast to the results by Gunton et al, 12 which suggests that a reduction in HIF expression in the islets contributes to the b-cell dysfunction in type 2 diabetes. 12 In the same study, it was reported that knockdown of HIF-1a in Min6 cells leads to impaired glucose-stimulated insulin secretion.…”
Section: Discussioncontrasting
confidence: 70%
“…45,46 Indeed, previous studies have shown that hypoxia impairs insulin secretion. 52,53 Thus, these studies along with our findings and others, 27,41,42 which all show impaired b-cell function with VHL loss, are in contrast to the results by Gunton et al, 12 which suggests that a reduction in HIF expression in the islets contributes to the b-cell dysfunction in type 2 diabetes. 12 In the same study, it was reported that knockdown of HIF-1a in Min6 cells leads to impaired glucose-stimulated insulin secretion.…”
Section: Discussioncontrasting
confidence: 70%
“…Previous work has demonstrated that hypoxia impairs insulin secretion (32)(33)(34). VHL inactivation, via HIF-1␣ stabilization, mimics certain aspects of the cellular response to hypoxia, and canonical target genes of the HIF complex, including Vegf and Glut1, are significantly upregulated in VHL-depleted islets.…”
Section: Discussionmentioning
confidence: 99%
“…in 29). Defects in ATP production have been linked to impairment of insulin secretion in response to glucose (27,33,35). Furthermore, mitochondrial mutations that result in decreased ATP production have been linked to diabetes in humans (36 -38).…”
Section: Discussionmentioning
confidence: 99%
“…For example, oxygen‐deprived chondrocytes have been found to produce increased quantities of collagen type I, which leads to suboptimal cartilage properties (Lewis et al ., ; Murphy and Polak, ). Insulin secretion by pancreatic islet cells has been found to decrease as local oxygen content decreases (Narimiya et al ., ). Although cells generally reduce their metabolism in response to low oxygen (thus reducing oxygen requirements) by partially converting from aerobic to anaerobic metabolism (Koh et al ., ), this switch increases glucose requirements for energy and increases lactic acid production, which in turn decreases local pH and may cause tissue necrosis (Brown et al ., ).…”
Section: Hypoxia and Tissue Engineeringmentioning
confidence: 97%